Clearing the Hurdles Women Building High-Growth Businesses. - Brush, Candida G.; Carter, Nancy M.; Gatewood, Elizabeth; Greene, Patricia G.; Hart, Myra M. (Financial Times/Prentice Hall Pearson Education [Distributor], 2004)
Annotation